Neutron Activation Analysis of the Metals From Ancient Coins Dating Back to Roman Age - Mukhamedshina, N.; Başaran, S.; Mirsagatova, A. A.; Bolcal, Ertuğrul Cem; Güleç, A.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (ASIAN JOURNAL OF CHEMISTRY, 11/100 RAJENDRA NAGAR, SECTOR 3,, SAHIBABAD 201 005, GHAZIABAD, INDIA, 2007)
Concentration levels of various elements have been estimated in ancient coins dating back to Roman age, which have been found in a sewage system of the ancient Ainos (Enez, Turkey). The coins are distributed into two groups on the basis of elemental composition: Pb and Cu based or Fe and Mn based coins indicating that two different ore deposits were used for issuing these coins. Other minor elements present in varying proportions are Ca, As and n. Besides to these major and minor elements, the coins,,were found to contain Na, K, Sc, Cr, Co, Ni, Zn, Br, Ag, Sb, Ba, An as impurities.
Keywords: Neutron Activation Analysis; Ancient Coins; Archaeometry; X-ray-fluorescence; Nötron Aktivasyon Analizi; Antik Sikke; Arkeometri; X-ışını Flüoresans